Swot Analysis And Consumer Satisfaction Of Broiler Marketing In Pringsewu Utara Village, Pringsewu District, Lampung - Rifki Ramadhan Novriansyah; Tri Rumiyani; Imelda Panjaitan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Broilers are a vital livestock species in Indonesia, providing essential food for the population's nutritional needs. Their rapid production cycle, direct marketability, high productivity, low costs, and yearly increase in demand make them popular among diverse demographics. Benefits include accelerated growth, feed efficiency, and superior meat quality. Broilers are also affordable and offer numerous business prospects. Marketing is a critical aspect of operating and advancing a firm, aiming to provide products or services to the right consumers at the right location, at the optimal time, and in a manner that benefits both producers and consumers. A marketing strategy is a set of goals, objectives, policies, and processes that guide marketing efforts across time and locations. Common issues in the broiler sector include high competition and pricing adjustments, driven by seasonal volatility in livestock commodity production. Seasonal uncertainty results in price fluctuations when supply is low but demand is steady, and when supply grows while demand is steady or low, prices fall. SWOT analysis is a method used to evaluate problems, projects, or business concepts based on internal elements (strengths and weaknesses) and external factors (opportunities and threats). Consumer satisfaction is a crucial component in generating loyalty and sustaining market share. Factors determining consumer satisfaction include courteous service, rapid delivery, and fresh broiler items. To achieve customer satisfaction, a comprehensive strategic approach is needed, considering factors such as product quality, pricing, availability, service, and the relationship between producers and consumers. The study purpose was analyze the internal factors (strengths and weaknesses) of broiler marketing in Pringsewu Utara Village, identifying external factors (opportunities and threats) that influence broiler marketing in Pringsewu Utara Village, assessing consumer satisfaction with broiler products in North Pringsewu Village, determine the right marketing strategy based on SWOT analysis. The research was conducted in April–May 2025 using purposive sampling, involving broiler business owners and consumers. Data were collected through observation, interviews, documentation, and literature studies. Analysis methods included Matrix Internal Factor Evaluation (IFE), Matrix External Factor Evaluation (EFE), Matrix Strengths, Weaknesses, Opportunities, Threats (SWOT) and Customer Satisfaction Index (CSI). Results show that the broiler marketing position is favorable, with strong internal and external conditions supporting aggressive growth strategies. The CSI value of 79.28% indicates that overall consumers are satisfied with the broiler marketing attributes in Pringsewu Utara. It can be concluded that the marketing position of broilers is very favorable thanks to good internal and external conditions. This can be seen from the strengths and opportunities that can be effectively utilized through aggressive growth strategies. The Customer Satisfaction Index (CSI) value of 79.28% indicates that consumers are overall satisfied with the marketing attributes of broilers in North Pringsewu Village.